A proposal for the learning of quantum physics based research in science education - Jordi Solbes; Vicente Sinarcas (Revista de Enseñanza de la Física, 2010)
In this work a proposal is presented for the quantum physics teaching that includes all the conceptual aspects of procedure and STS relations that are necessary to have into account for getting a signifi cant learning of the pupil and a change in his attitude, like investigation in didactics of the sciences shows.